The Impact of Strategic Cohesion on Administrative Excellence - Hussein Jassem, Thuraya; Abdel-Wadoud Taher, Adel (Journal of Economics and Administrative Sciences, 2024)
This research aims to test the effect of strategic cohesion with its dimensions (organizational excitement, organizational casting, organizational synergy) as an independent variable on administrative excellence as a dependent variable in the Ministry of Planning, and through surveying several employees (general managers, heads of departments,  and units managers). As a research community, and based on the importance of the research topic in the aforementioned research community. The researchers have adopted the descriptive-analytical using the questionnaire as the main data collection. 155 questionnaires were distributed, yet,114 of them were retrieved and 110 were used for final statistical analysis. The researchers used the relevant standard statistical methods, for example, “(confirmative and exploratory factor analysis, coefficient of variance, and relative importance). To test the hypotheses and a number of statistical measurements based on them (SPSS, AMOS V.25)), the researchers depend on the (Kolmogorov – Smirnov test), The most prominent result is that strategic cohesion with its dimensions impact on administrative excellence. The most important recommendation is that there is a need for the Ministry of Planning to adopt strategic cohesion and focus on it to reach the excellence that the ministry seeks to reach its goals, vision, and mission. Paper type:  Research paper.